PENGARUH PROPORSI SARI JAHE MERAH DAN SARI KAYU MANIS TERHADAP TINGKAT KESUKAAN SARABBA INSTAN - Sindy Claudia Tira’ Tangkeallo; Yoakhim Y. E. Oessoe; Jan R. Assa (COCOS, 2023)
ABSTRACTThis study aims to evaluate the level of preference of panelists including color,taste and aroma of instant sarabba. The research method used was a completelyrandomized design (CRD) method with 4 treatment levels of the proportions ofred ginger extract and cinnamon extract namely A (100% : 0%), B (95% : 5%), C(90% : 10%) ) and D (85% : 15%) with 3 repetitions. The preference level testuses the hedonic scale to determine the product's sensory value in terms of color,taste and aroma. The results showed that the level of preference for color rangedfrom 3.68 - 4.00, for aroma ranged from 3.48 - 4.96 and for taste ranged from3.88 - 4.08Keywords: Sarabba, Red Ginger, Cinnamon.